Modeling and Measuring the Structure of Professional Vision in Preservice Teachers - Seidel, Tina; Stürmer, Kathleen (American educational research journal, 2014)
Professional vision has been identified as an important element of teacher expertise that can be developed in teacher education. It describes the use of knowledge to notice and interpret significant features of classroom situations. Three aspects of professional vision have been described by qualitative research: describe, explain, and predict classroom situations. We refer to these aspects in order to model professional vision. We developed a video-based instrument to empirically test the model. The results show that our measure to assess aspects of professional vision differentiates between description, explanation, and prediction. The study provides insight into the structure of professional vision, allowing us to conceptualize it theoretically and discuss the targeted use for teaching and formative assessment of preservice teachers.